UKURAN PERUSAHAAN, MODAL KERJA, DAN RETURN ON EQUITY (ROE) PADA INDUSTRI OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) SELAMA PERIODE 2012-2015 - Fe Fe; Arna Suryani (Ekonomis: Journal of Economics and Business, 2017)
This research aims to find out how the effect of the firm size and working capital towards Return on Equity (ROE) in the automotive industry are listed on the Indonesia Stock Exchange (IDX) during 2012-2015 periods. Tthe data used are secondary data, which uses quantitative descriptive analysis method by using multiple linear regression analysis and statistical tests the F test and t test. Based on multiple linear regression analysis results with the data panel obtained equations Yit = 1746.027 – 6.932X1it + 0.440 X2it + µit. Based on simultaneous test (F) Firm Size and Working Capital effect significantly to Return on Equity. Based on the partial test (t) Firm Size and Working Capital effect significantly to Return on Equity. The results of the R Square is 0.151 or 15.1%. Means of 84.9% explained by other factors outside of research.Keywords :Firm Size, Working Capital, Return on Equity